STILISTIKA PADA LAGU TANDA KARYA YURA YUNITA - Wiwik Surya Utami (Universitas Batanghari, 2025)
Language and style have a close and complementary relationship, where style is an art of using language while language provides structure and function, as well as color and appeal. Therefore, the combination of the two makes both spoken and written language more effective, beautiful, and meaningful. The purpose of this research is to describe the style and meaning found in the lyrics of the song 'Tanda' sung by Yura Yunita using a stylistic approach. The results of this study show that the use of style and effective word choice or diction can create an emotional and aesthetic atmosphere. The stylistic approach reveals how the choice of words, sentence structure, and the use of the repetition style in Yura Yunita's song 'Tanda' give birth to a language style featuring 2 styles of repetition, 2 styles of anaphora, and 1 style of epanalepsis. The language style in the song contributes to its meaning. A deep song that resonates in the minds of listeners. The use of poetic and imaginative language creates a rich aesthetic experience for listeners, while also reinforcing the song's message about longing, hope, and the search for identity. In the lyrics of the song 'Tanda', a positive connotative meaning is found, showing a servant's request to their God for guidance regarding the right path and the fulfillment of every prayer uttered by the lyricist. The song 'Tanda' by Yura Yunita is a good example of how stylistic elements can be used to enhance the appeal and effectiveness of a work.